The Swedish Budget : 1974/75 a summary - Sweden, Finance department (Stockholm : [s.n.], 1974)
This twelfth edition of the Swedish Budget contains a summary of the Draft Budget for fiscal 1974/75, giving a complete translation of the Budget Statement as well as an account of the composition and orientation of central government expenditure and revenue.
Includes bibliographical references
usc 15/08/2019
Loans
Keywords: Budget; Economic history; Sweden